Methods of calculation and strengthening wire anchor systems and devices for their installation - Zamir G. Lamerdonov; Tatiana Yu. Khashirova; Inna A. Zhirikova (Мелиорация и гидротехника)
Purpose: calculation substantiation of forces acting on wire anchor systems, as well as development of devices for their installation. Materials and methods. Recently, anchor systems have been increasingly used in construction, especially in the field of environmental technologies. It is proposed to install anchor systems using vibratory hammers, impact beams, and by blockage guide rods to a great depth. Currently, wire anchors with conical tips, which have proven their efficiency and practical reliability, are actively used. The main research method is a theoretical approach. Results. Based on the static equilibrium equation, formulas for determining the pulling force are obtained. Active forces are the forces that pull out the wire anchor, while reactive forces determine the weight of the soil and the resistance that occurs during the pulling out process. The technologies for installing wire anchors, the systems of which have great potential for use in agriculture are presented; they are used to strengthen dam slopes. Conclusions. The improved designs of wire anchors and anchor systems which are used to increase bearing and static stability have been developed. A method for installing wire anchors including methods for blockage using specialized vibratory hammers and impact tools (hammers) has been developed. Calculation methods for wire anchors, reinforced structures and anchor systems, both flat and spatial, are proposed.